Criminal penalties for company board members for misuse of company funds - Osama Jari Al-Mutairi; Mustafa Mohammed Bitar (International Journal of Law Research and Studies, 2025)
The study aims to analyze and compare the texts of criminalization and punishment for the criminal liability of members of the company's board of directors in the Saudi and Emirati systems. And to distinguish the crime of misuse of company funds from other crimes of corporate funds, which the Saudi and Emirati regulators have introduced and set penalties for, including the crime of misuse of company funds, the crime of distributing fictitious profits, the crime of fraudulent bankruptcy, and the crime of abuse of authority and votes in the company. Despite the differences in the methods of committing them, they fall within one scope, which is the misuse of company funds. Hence, the importance of the study comes in that it seeks to determine who is responsible for crimes committed in the name of the company. The problem of the study is represented in the following question: What is the criminal liability of members of the board of directors of companies for the misuse of funds in the Saudi and Emirati systems? The study reached a set of results, the most important of which is that the Saudi and Emirati systems did not use the term misuse of funds, but rather used the use of company funds against the interests of the company to express the crime, but this crime was known in criminal jurisprudence by two names, which are; The crime of misuse of company funds and the crime of abuse of company funds. The two systems agreed on the punishment of imprisonment for a period not exceeding three years for the crime of misuse of funds, and the two systems differed in the estimated fine, as the Saudi commercial system is considered higher in fine. The UAE legislator also agreed with the Saudi regulator on the necessity of the availability of the special criminal intent represented in the use of company funds to achieve personal interest.
Keywords: Crimes of Board Members; Misuse of Company Funds; Corporate Crimes